﻿The Struggle for Ownership of Assistance - Rwangombwa, John (World Bank, 2012)
Aid earmarking reflects donor priorities more than those of the recipient country. Rwanda has sought to reform its health care system, while donor funding was focused on fighting HIV/AIDS.